Reply to Letter to the Editor: The Invasive Caribbean Mytilopsis sallei (Bivalvia: Dreissenidae): A Short Review - Koh Siang Tan; Teresa Tay (ASEAN Journal on Science and Technology for Development, 2020)
This letter provides a response to the letter concerning "The Invasive Caribbean Mytilopsis sallei (Bivalvia: Dreissenidae): a Short Review" by Tan and Tay in AJSTD 35(1–2): 133–139.